THE MULTI-SCREEN AESTHETICS IN THE ANIMATED CARTOONS OF SOVIET ARTISTS / ПОЛИЭКРАННАЯ ЭСТЕТИКА В МУЛЬТИПЛИКАЦИИ СОВЕТСКИХ ХУДОЖНИКОВ - EVALLYO VIOLETTA DMITRIEVNA / ЭВАЛЛЬЕ ВИОЛЕТТА ДМИТРИЕВНА (Наука телевидения)
The essence of the multi-screen technique is to divide, however, paradoxically, it unites objects and spaces, juxtaposes them, and generates new means of interaction. The multi-screen technique reflects the structure of the spatial position of the protagonists and the map of the heroes’ social space, helps trace out their characters in greater detail and to bring in other protagonists smoothly. In the present article the author examines for the first time the aesthetical constituent of the multi-screen phenomenon in authorial animation of the late Soviet period on the example of the animated cartoons “Istoriya odnogo prestupleniya” [“The Story of One Crime”] and “Film, film, film” by Feodor Khitruk, “Lisa i zayats” [“The Fox and the Rabbit”] by Yuri Norstein, and “Kontakt” [“Contact”] by Vladimir Tarasov. The multi-screen technique in these works veils the reflected modernity and enhances the decorative and entertaining traits of the visual matter. By means of the “play” of the cadres and windows not only expansion of the semantic connotations is achieved, but the originality of the “picture” is heightened. The multi-screen technique presents the film producer with the unique opportunity of both demonstrating the difference of the protagonist’s perception of the world and enhancing the semantical implications. The author examines in detail the multi-screen episodes and effects of the multi-screen techniques implemented into the visual narration, noting them as serving as a reflection of the picture of the world of that time period, and accentuates the interest in the human being, his inner world with the expression of the authorial philosophical-aesthetical position in the structure of the film. Thereby, all the visual and scenic components of the animated cartoon in general and the multi-screen technique in particular work on the creation of a profound ethical-aesthetical work, multiple in its interpretation.